Pengaruh Kepemilikan Institusional, Profitabilitas, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Zahra, Raudhatul; NR, Erinos (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to determine the influence of institutional ownership, profitability and company size on company value. profitability, and company size on company value. Sample selection used a purposive sampling method, which resulted in a sample of 56 manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Statistical analysis used multiple linear regression with SPSS 25. The results of the analysis showed that institutional ownership, profitability and company size had a significant effect on company value. Based on simultaneous results, Institutional ownership, profitability, and company size have an impact on company value.